Teachers’ Strategies in Instilling Religious Character in Adolescents in the 5.0 Era at SMK ICB Semarang - Husna, Najwa Nailal; Aang Kunaepi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
The Society 5.0 era presents challenges for Islamic education, particularly in maintaining adolescents’ religious character amid rapid digitalization. This study aims to analyze teachers’ strategies in instilling religious character at SMK Islamic Centre Baiturrahman Semarang by integrating spiritual practices with technology-based approaches. Using an intrinsic case study design, data were collected through interviews, observations, and documentation involving four teachers and twenty Year 11 students, and analyzed thematically. The findings reveal a Four-Dimensional Religious Character Formation Model, consisting of: (1) role modelling, in which teachers demonstrate consistent Islamic behavior and worship practices; (2) worship habituation, through structured religious routines and extracurricular activities; (3) technology-integrated character learning, involving digital religious media, Islamic applications, and project-based digital content; and (4) religion-based school culture reinforced through teacher, student, parent collaboration. These dimensions collectively strengthen students’ spiritual awareness, digital responsibility, and ethical behavior in daily life. This study contributes a contextual and adaptive framework for Islamic character education relevant to the Society 5.0 era, with implications for the development of technology-supported religious pedagogy and institutional character-building policies. Limitations regarding school context, technological facilities, and variations in student religiosity indicate the need for broader and comparative research.